Can mobile phones improve gender equality and nutrion? Panel data evidence from farm households in Uganda - Haruna Sekabira; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
During the last 10-15 years, mobile phone technologies have been widely adopted in most developing countries, including adoption by rural households that never had access to landline phones before. Existing research shows that use of mobile phones has improved market access for smallholder farmers and thus household income. Beyond income, mobile phones can possibly also affect other dimensions of social welfare, such as gender equality and nutrition. Such broader social welfare effects have hardly been analyzed up till now. Here, we address this research gap, using panel data from smallholder farm households in Uganda. Regression results show that mobile phones have significantly contributed to household income gains and women empowerment. Mobile phone use has also improved household food security and dietary quality. Simultaneous equation models are estimated to show that the positive nutrition effects are primarily channeled through the influence of mobile phones on household income and gender equality. Gender disaggregation reveals that female mobile phone use has stronger positive welfare effects than if males alone use mobile phones. We conclude that equal access to mobile phones cannot only foster economic development, but can also contribute to gender equality, food security, and broader social development.
Keywords: I15; O16; O33; Q12; 330; mobile phones; women empowerment; dietary diversity; Uganda; gender; incomes